ChemInform Abstract: New Antiferromagnetic Perovskite CaCo3V4O12 Prepared at High‐Pressure and High‐Temperature Conditions. Issue 1 (7th January 2014) - Ovsyannikov, Sergey V.; Zainulin, Yury G.; Kadyrova, Nadezda I.; Tyutyunnik, Alexander P.; Semenova, Anna S.; Kasinathan, Deepa; Tsirlin, Alexander A.; Miyajima, Nobuyoshi; Karkin, Alexander E.
Abstract The new title perovskite is synthesized from mixtures of Ca(VO3)2, Co(VO3)2, and Co (14—18 GPa, 900—1300 °C, 0.5—8 h).